EUROPEAN EXPERIENCE OF TRAINING OF FUTURE TEACHERS OF FOREIGN LANGUAGES: FINDINGS AND PROSPECTS FOR UKRAINE - Bezliudna Vita V.; Shcherban Iryna Yu.; https://orcid.org/0000-0002-9918-7711; Makarchuk Victoriya V. (Scientific Journal of Pedagogy and Economics, 2020)
The aim of the paper is to analyze the peculiarities of training of future foreign languages teachers of some European countries and generalize the useful European experience, which can be recommended as prospects for improving the training of future foreign languages teachers in Ukrainian higher educational establishments. The study was conducted using methods of analysis, synthesis, generalization, comparative analysis and predictive methods. The main focus of this study is on the analysis of the experience of training future teachers of foreign languages in higher educational institutions in the following European countries: Germany, France, Poland, Switzerland, Italy, the Czech Republic, Hungary, Finland, Estonia. A comparative analysis of the system of foreign language education in European countries allowed the authors to identify general and specific features of the training of future teachers of foreign languages in European countries, as well as highlight the models in the structure of training of future teachers of foreign languages: Bachelor-teacher, Bachelor-linguist, Master, which indicates the wide variability and dynamism of the development of the training system of future teachers of foreign languages in Europe. The generalization of the European experience in the training of future teachers of foreign languages gave the authors the opportunity, to find out fundamentally important directions, to formulate the main recommendations as the prospects for improving the training of future teachers of foreign languages at Ukrainian higher educational establishments at the level of educational policy of Ukraine